2019
DOI: 10.1016/j.pvr.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

False positive cervical HPV screening test results

Abstract: In cervical cancer screening, HPV testing is best at reassuring women when they are negative, but proper management of HPV positives is still evolving. Most HPV infections are benign, and over-reacting clinically to HPV positivity can cause psychological and possible iatrogenic physical (e.g., obstetrical) harm. We describe the built-in false positives in current tests, and the real harm that can result when the meaning of such false positive HPV tests is misunderstood. We suggest steps that could reduce harm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…So far, a large number of methods for screening CIN or early CC have been developed, such as HPV DNA testing [8], papanicolaou (pap) smear [9], liquid-based cytology (LBC) [10], joint test, and colposcopy, leading to the reduction of the incidence and mortality rate of CC [11][12][13]. Nevertheless, existing screening methods were complained of some limitations, including false-positive rate [14] or false-negative rate [15][16][17], possibility of overdiagnosis [18], probability of missed diagnosis [19], invasive procedure (cervical scraping or tissue biopsy), the difference between interobserver and intraobserver, and variation among pathologists [20], which made the triage of screening CC more complicated [21]. Therefore, it is extremely imperative to find simple, noninvasive, and feasible biomarkers for identification of CIN and early CC.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a large number of methods for screening CIN or early CC have been developed, such as HPV DNA testing [8], papanicolaou (pap) smear [9], liquid-based cytology (LBC) [10], joint test, and colposcopy, leading to the reduction of the incidence and mortality rate of CC [11][12][13]. Nevertheless, existing screening methods were complained of some limitations, including false-positive rate [14] or false-negative rate [15][16][17], possibility of overdiagnosis [18], probability of missed diagnosis [19], invasive procedure (cervical scraping or tissue biopsy), the difference between interobserver and intraobserver, and variation among pathologists [20], which made the triage of screening CC more complicated [21]. Therefore, it is extremely imperative to find simple, noninvasive, and feasible biomarkers for identification of CIN and early CC.…”
Section: Introductionmentioning
confidence: 99%
“…The HPV test was performed with the Hybrid Capture 2 test technology (HC2; Qiagen, Gaithersburg, MD, USA) which detects 13 high-risk HPV types: 16,18,31,33,35,39,45,51,52, 56, 58, 59 and 68. A positive result was considered if attained or exceeded the FDA-approved threshold of 1.0 relative light unit (RLU/CO).…”
Section: Screening Tests and Gold Standard Testmentioning
confidence: 99%
“…However, having a screening test with a higher sensitivity but a lower specificity leads to overdetection and needs to be balanced by the benefits of an early detection. To avoid detection of HPV positive cases that are unlikely to develop cervical cancer, several authors have proposed to restrict the number of HPV types included in the HPV assays, given that the risk of developing a CIN3+ is very low for some genotypes such as 39, 51, 56, 59, 68 [33,34]. Recent studies have seen that the risk of developing a 7-year CIN3+ for these types is less than 5% and 80% of these infections are no longer detected in three years [34].…”
Section: Plos Onementioning
confidence: 99%
“…It also captured other less carcinogenic types such as HPV 39, 59, 68, 51 and 56, as in the study performed by Secondy et al 35 The higher HPV positivity rate found by care HPV could be due to the test’s ability to identify these less carcinogenic HPV types. This may be associated with a waste of resources, which may especially be a problem in LMICs, where economic means are constrained 16 . While bearing this in mind, limiting the range of HPV types in the care HPV test to the most carcinogenic ones to improve the cost‐effectiveness of the testing might be considered.…”
Section: Discussionmentioning
confidence: 99%